Ecological responses by Mexican spotted owls to environmental variation in the Sacramento Mountains, New Mexico - Ward, James P., Jr., author; Van Horne, Bea, advisor (Colorado State University. Libraries, 2001)
Understanding the influence of environmental variation on population processes is a fundamental requisite for devising strategies that conserve species. A common tactic for conserving raptor populations is to maintain or manipulate habitat conditions that maintain or increase availability of prey species. A primary purpose of this investigation was to evaluate the hypothesis that Mexican spotted owls (Strix occidentalis lucida) could be conserved by manipulating microhabitat conditions that increased abundance of one or more common prey species. I evaluated this hypothesis by (1) determining which common prey were preferred by this owl, (2) which prey species were most likely to influence the owl's reproduction, and by assessing (3) which prey species were most likely to increase in abundance following microhabitat manipulation. In addition to prey availability, I also examined the influence of two other likely sources of environmental variation, weather and macrohabitat condition, on spotted owl reproduction and common prey abundance. The investigation focused on one population of Mexican spotted owls over a six-year period (1991-1996) in the Sacramento Mountains, New Mexico; an area where vegetation communities have been modified extensively over the past 100 years. Under current landscape conditions, I found that these Mexican spotted owls consumed a variety of prey species during the breeding season. However, five murid rodents were most common. These included the deer mouse (Peromyscus maniculatus), brush mouse (P. boylii), Mexican vole (Microtus mexicartus), long-tailed vole (M. longicaudus), and Mexican woodrat (Neotoma mexicana). Depending on the year of study, the five species accounted for 53-77 % of frequency of all items recovered from samples of regurgitated pellets and 41-66 % of biomass consumed by these spotted owls. Mexican woodrats were preferred among the five prey species. Absolute functional responses to available numbers of woodrats varied in form (a quadratic function) compared to responses to mouse (a linear function) and vole (an increasing but asymptotic function) abundance. Total available biomass (kg) of mice and voles provided the strongest correlation (r = 0.78, P = 0.07, n = 6 yrs) with reproductive output (number of young found per pair) of Mexican spotted owls among a suite of covariates that included measures of weather, macrohabitat quantity, and available prey biomass over the six annual periods. There was little evidence that selected weather variables and macrohabitat quantities were associated with the owl's reproductive output (all r < 0.50, P > 0.39). Models of factors associated with reproductive potential (number of young produced in a given owl territory relative to maximum number possible during all years the territory was sampled) indicated that precipitation during the nesting period (March-May) played a greater relative role (relative importance based on a weighted Akaike criterion [RI] = 0.733) in explaining a limited amount of variation (R2 of all models ≤23%) in the owl's reproduction among territories. Weaker evidence suggested that the owl's reproductive potential varied inversely among territories with warmer temperatures during late fall—winter (RI = 0.447) periods or colder temperatures during the early nesting period (RI = 0.335), and varied positively with available biomass of mice and voles (RI = 0.331). In the current landscape, available biomass of Mexican woodrats, the preferred prey, was not correlated with the owl's annual reproductive output nor its reproductive potential. Empirical models of factors that influence availability of these five common prey species indicated that the easiest species to influence through microhabitat manipulation would be the Mexican vole, followed by the long-tailed vole, Mexican woodrat, deer mouse, and lastly the brush mouse. The model results indicated that abundance (g/ha) of the two vole species could be influenced most readily by manipulating grass-forb height, whereas abundance of Mexican woodrats might be influenced by promoting shrub diversity and increasing large (≥30-cm diameter) log cover. Increase of the two mouse species was considered more difficult because of their association with seed or mast crops, which were influenced by uncontrollable variables like previous amounts of precipitation, or their association with microhabitat variables like rock cover. Details regarding historical and current conditions in the study area and comparisons between a mixed-conifer, late-seral plot and a mid-seral plot indicated that microhabitat variables associated with Mexican woodrat abundance and the amount of woodrat biomass available to Mexican spotted owls likely declined with past timber harvest. Consumption of woodrats by spotted owls in the Sacramento Mountains was the lowest among reported studies of spotted owl feeding habits. When examined across eight different populations of spotted owls, consumption of woodrat biomass (%) was found to be inversely related to temporal variability in the owl's reproductive output (R2 = 0.66, 95% CI [β1] = -0.941 to -0.163). I therefore proposed that future management of habitat condition in the Sacramento Mountains should strive to reduce temporal variation in Mexican spotted owl reproduction by increasing abundance of Mexican woodrats, which may be possible through experimental manipulations of mid-seral mixed-conifer stands. The immediate objective of these manipulations would be to enhance key microhabitat features required by Mexican woodrats such as shrub evenness and den sites or foraging cover. These manipulations appear to be congruent with current demands to thin overstocked, mixed-conifer stands in the study area. By conducting these manipulations as experiments and monitoring the associated responses by Mexican woodrats and Mexican spotted owls, a more comprehensive understanding of effects of environmental variation on this predator-prey system can be gained.
Keywords: ecology; forestry; zoology